Philippine Sin Tax Law evaluation effectiveness in healthcare financing - Orallo, Luis Sebastian C.; Tayao, Anthony Benedict S.; Mendoza, Maria Nimfa (Quezon City School of Economics, University of the Philippines Diliman, 2021)
Republic Act No. 10351, otherwise known as the Sin Tax Reform Law, was enacted last December 2012 under the Aquino Administration. The law aims to lessen the consumption of alcohol and tobacco products in an effort to eliminate unwanted behavior among Filipinos. By increasing the tax and price of these products, their consumption would theoretically decrease. Another goal of this law was to use its revenues to compensate Filipinos' health finances, particularly that of the Philippine Health Insurance Corporation (PhilHealth) premiums. RA No. 10351 has two phases, the first being incrementally increasing the taxes of alcohol and tobacco products. The second phase adds an annual 4% increase to these taxes. This paper will analyze the period before the law's implementation and the first phase of the Sin Tax Reform Law, which took effect from 2013 to 2017. With several factors to consider, it is vital to understand how this policy contributes in financing one of the country's most important systems. This will be analyzed by conducting a multivariate ordinary least squares (OLS) regression on out-of-pocket health expenditures and burden of health payments. Also, a tobit regression will also be utilized to determine the effects of households reporting PHP 0 on their Out_of_pocket expenses. The researchers gathered data from the Family Income and Expenditure Survey (FIES) for the years 2012 and 2015. With that, the researchers will be able to evaluate the effectiveness of the Sin Tax Reform Law and its connection towards healthcare financing. The results demonstrated that during the incremental tax addition phase in 2015, the Sin Tax Reform Law was significantly able to decrease household's burden of health payments, but not as much as compared to before the law's implementation. For household's out-of-pocket health spending alone, a decrease smaller than that of the period before the law's implementation was also observed.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Philippines -- Republic Act No. 10351 (Sin Tax Reform Law of 2012).; Drinking of alcoholic beverages -- Economic aspects -- Philippines; Tobacco use -- Economic aspects -- Philippines; Medical care -- Finance -- Philipppines